UDP-Glucuronic Acid Transport Is Required for Virulence of Cryptococcus neoformans - Lucy X. Li (American Society for Microbiology, 2018)
ABSTRACT Glycans play diverse biological roles, ranging from structural and regulatory functions to mediating cellular interactions. For pathogens, they are also often required for virulence and survival in the host. In Cryptococcus neoformans, an opportunistic pathogen of humans, the acidic monosaccharide glucuronic acid (GlcA) is a critical component of multiple essential glycoconjugates. One of these glycoconjugates is the polysaccharide capsule, a major virulence factor that enables this yeast to modulate the host immune response and resist antimicrobial defenses. This allows cryptococci to colonize the lung and brain, leading to hundreds of thousands of deaths each year worldwide. Synthesis of most glycans, including capsule polysaccharides, occurs in the secretory pathway. However, the activated precursors for this process, nucleotide sugars, are made primarily in the cytosol. This topological problem is resolved by the action of nucleotide sugar transporters (NSTs). We discovered that Uut1 is the sole UDP-GlcA transporter in C. neoformans and is unique among NSTs for its narrow substrate range and high affinity for UDP-GlcA. Mutant cells with UUT1 deleted lack capsule polysaccharides and are highly sensitive to environmental stress. As a result, the deletion mutant is internalized and cleared by phagocytes more readily than wild-type cells are and is completely avirulent in mice. These findings expand our understanding of the requirements for capsule synthesis and cryptococcal virulence and elucidate a critical protein family. IMPORTANCE Cryptococcus neoformans causes lethal meningitis in almost two hundred thousand immunocompromised patients each year. Much of this fungal pathogen’s ability to resist host defenses and cause disease is mediated by carbohydrate structures, including a complex polysaccharide capsule around the cell. Like most eukaryotic glycoconjugates, capsule polysaccharides are made within the secretory pathway, although their precursors are generated in the cytosol. Specific transporters are therefore required to convey these raw materials to the site of synthesis. One precursor of particular interest is UDP-glucuronic acid, which donates glucuronic acid to growing capsule polysaccharides. We discovered a highly specific, high-affinity transporter for this molecule. Deletion of the gene encoding this unusual protein abolishes capsule synthesis, alters stress resistance, and eliminates fungal virulence. In this work, we have identified a novel transporter, elucidated capsule synthesis and thereby aspects of fungal pathogenesis, and opened directions for potential antifungal therapy.